Psychische Verluste des hohen Alters, kognitive Reserve, strukturelle Resistenz - Janzarik, Werner (Der Nervenarzt, 2012)
Summary Losses of mnestic and other competencies in very old persons are presently being studied from different perspectives, e.g., neurobiological, neuropsychological, and phenomenological ones. In this context the concept of cerebral and cognitive reserve has been formulated. From a personalist perspective the concept of structural resistance should be added, which is based on central dispositions in personality structure and determines the capacity to find ways to navigate through the losses in advanced age, and the dynamics to follow these paths.
Online publiziert 19. Oktober 2011
Gesehen am 14.08.2018